Transition of Akabane virus genogroups and its association with changes in the nature of disease in Japan. Issue 2 (29th November 2017) - Yanase, T.; Kato, T.; Hayama, Y.; Akiyama, M.; Itoh, N.; Horiuchi, S.; Hirashima, Y.; Shirafuji, H.; Yamakawa, M.; Tanaka, S.; Tsutsui, T.
Summary: Akabane virus (AKAV) is teratogenic to the foetus of domestic ruminants and causes a significant reproduction loss in cattle in Japan. In several past epizootics in cattle, AKAV was also associated with post‐natal encephalomyelitis, mainly in calves and young stock. Previously analysed AKAV isolates in East Asia form two major clusters, genogroups I and II, with isolates involved in encephalomyelitis belonging mainly to the former. Between 2007 and 2013, AKAV epizootics were regularly observed in Japan during the summer/autumn season, and abnormal deliveries and post‐natal encephalomyelitis caused by the virus in cattle were reported. During this period, 30 AKAV isolates were obtained from diseased and sentinel cattle, a piglet and Culicoides biting midges throughout Japan and were subjected to genetic comparison and phylogenetic analysis with previous isolates. In 2007, 2011 and 2013, AKAV belonging to genogroup I was identified in the central nervous systems of calves showing neurological disorders. Notably, a total of 165 cases of bovine encephalomyelitis were reported in 2011 and the isolated viruses from affected animals shared high genetic identities with a South Korean isolate that was associated with a large outbreak in 2010, suggesting some epidemiological linkage between these epizootics. Epizootics of genogroup II were observed in 2008 and 2010, but bovine post‐natal encephalomyelitis cases rarely occurred. Our findings suggest that the frequent incursion of genogroup I isolates has increased the frequency of post‐natal encephalomyelitis cases in Japan in recent years. Infection by genogroup I virus was also identified in piglets with neurological disorders or congenital malformations in 2011 and 2013. The aetiological role of AKAV in pigs should be elucidated in the future.